Intelligent energy management: Evolving developments, current challenges, and research directions for sustainable future. (10th September 2021) - Ali, Muhammad; Prakash, Krishneel; Hossain, Md Alamgir; Pota, Hemanshu R.
Abstract: In the last decade, there have been significant developments in the field of intelligent energy management systems (IEMSs), with various methods and new solutions proposed for managing the energy resources intelligently. An important issue related to finding the desired outcomes remains unexplored, i.e., how to determine key insights from the sparse academic literature in the age of digital publishing. To mitigate the issue, this study proposes a novel strategy to systematically survey the relevant studies by converting the sparse literature into visual presentations. We first apply a systematic approach called a PRISMA (Preferred Reporting Items for Systematic reviews and Meta-analyses) statement to provide the insights from the published literature of the past decade (2010–2020). Then, VOSviewer experiments are conducted to transform these sparse scholarly data into visual representations. In total, eighty-one papers published in high-impact journals are identified based on their scientific soundness and relevance, and a VOSviewer analysis is applied. The analysis revealed the existence of three research clusters focused on the following main thematic areas: the energy management in smart homes and smart grids (35 journal papers); the emerging concept of context-awareness (26 journal papers); and the role of privacy preservation in IEMSs (20 journal papers). This analysis uncovers the current state of IEMSs and explores existing issues, methods, findings, and gaps. Thus, future research directions have been recommended to fill the existing gaps. This systematic literature review is to assist both researchers and industry practitioners to understand the research gaps of previous studies. Highlights: Latest developments in energy management systems are compiled from scientific and practical perspectives. A new way to conduct systematic reviews is presented by combining PRISMA approach and VosViewer analysis. The sparse literature is converted into visual representations to quickly identify the research gaps from published literature. Emerging topics such as context-aware energy management, smart homes and smart grids, and the role of privacy preservation in energy management systems are explored. Existing research gaps are highlighted with potential solutions. New perspectives in the field are proposed to fill the existing gaps.